Effects of different composed squat resistance training on legs strength and start power performance in college swimmers - Cho, C.J.; Tai, Y.J.; Wu, C.M.; Ye, C.C. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Many swimming competition results indicate that legs strength also influence turn performance, but how to improve by training still controversy. Therefore, the aim of this study was to realize the effect of six weeks different composed squat resistance training in addition to the habitual swimming program on legs strength (LS) and start power (SP) performance. Methods: Twenty college swimmers were average assigned to two groups according to 1RM legs strength, groups A (n= 10; age: 20.00 ± 3.40 y; body mass:70.27 ± 12.37 kg; height: 170.90 ± 6.24 cm; body fat: 23.66± 7.63%, GA) and groups B (n= 10; age: 20.80 ± 3.71 y; body mass:65.32 ± 10.65 kg; height: 168.40 ± 7.47 cm; body fat: 22.77±8.33%, GB) were trained two times a week for six weeks. In weeks 1-3 and 4-6, GA performed 65% 15RM plus 90% 4RM (Wathen, 1994) GB performed 90% 4RM plus 65% 15RM squat weight training. Body fat, LS, and SP (calculate with body mass, 5m push wall start time, and 75 kg•m/s for hp) were measured before and after training, t-test was applied to analyze these data in group and group. Results: The results of this study indicated that two groups were effective at increasing LS after training (p<.05), GA improved from 83 to 144.5kg, GB improved from 83 to 130kg. In SP, only GB improved from 3.14 to 3.60hp (p<.05), all the swimmers decreased body mass (67.79 to 66.92kg) and body composition (23.21% to 22.70%) significantly(p<.05). Discussion: Results suggested a positive effect of GA and GB training program, because of these swimmers did not accept the routine training before, so the different composed course should increase the strength, off season national football player correspond to have a positive influence (Brechue and Mayhew, 2012). GB set training program from muscle strength to endurance and significant increase in SP, which was in accordance with previous studies that the importance of lower body strength and power to start time (west et al., 2011),we did not find the same effect in GA, probably due to the testing distance and other start skills. Previous reports have found that sprint swimming performance was related to body mass, lean body mass(Geladas et al., 2005), this study showed that both training programs transferred fat to muscle mass and increased strength, further study need to consider the swimmers` lever, resistance training experience, and sprint performance test is necessary.